The Concept of Coupling in the Mammalian Circadian Clock Network. Issue 12 (29th May 2020) - Pilorz, Violetta; Astiz, Mariana; Heinen, Keno Ole; Rawashdeh, Oliver; Oster, Henrik
Abstract: The circadian clock network regulates daily rhythms in mammalian physiology and behavior to optimally adapt the organism to the 24-h day/night cycle. A central pacemaker, the hypothalamic suprachiasmatic nucleus (SCN), coordinates subordinate cellular oscillators in the brain, as well as in peripheral organs to align with each other and external time. Stability and coordination of this vast network of cellular oscillators is achieved through different levels of coupling. Although coupling at the molecular level and across the SCN is well established and believed to define its function as pacemaker structure, the notion of coupling in other tissues and across the whole system is less well understood. In this review, we describe the different levels of coupling in the mammalian circadian clock system – from molecules to the whole organism. We highlight recent advances in gaining knowledge of the complex organization and function of circadian network regulation and its significance for the generation of stable but plastic intrinsic 24-h rhythms. Graphical abstract: Image 1 Highlights: The harmonious circadian rhythms across the mammalian body are characterised by three levels of bidircetional coupling. The molecular coupling of the oscillatory gene/protein expression leads to a synchronised cellular rhythm. Cellular coupling is generated via signaling molecules coordinating internal rhythms across an organ. Systemic coupling enables a crosstalk of different clock-tissues.